Nutraceutical Difference between Two Popular Thai Namwa Cultivars Used for Sun Dried Banana Products - Donporn Wongwaiwech; Sudthida Kamchonemenukool; Chi-Tang Ho; Shiming Li; Tipawan Thongsook; Nutthaporn Majai; Duangporn Premjet; Kawee Sujipuli; Monthana Weerawatanakorn (Molecules, 2022)
Musa (ABB group) “Kluai Namwa” bananas (Musa sp.) are widely grown throughout Thailand. Mali Ong is the most popular Kluai Namwa variety used as raw material for sun-dried banana production, especially in the Bangkratum District, Phitsanulok, Thailand. The sun-dried banana product made from Nanwa Mali Ong is well recognized as the best dried banana product of the country, with optimal taste compared to one made from other Kluai Namwa varieties. However, the production of Mali Ong has fluctuated substantially in recent years, leading to shortages. Consequently, farmers have turned to using other Kluai Namwa varieties including Nuanchan. This study investigated the nutraceutical contents of two popular Namwa varieties, Mali Ong and Nuanchan, at different ripening stages. Nutraceuticals in the dried banana products made from these two Kluai Namwa varieties and four commercial dried banana products were compared. Results indicated that the content of moisture, total sugar, and total soluble solids (TSS) (°Brix) increased, while total solids and texture values decreased during the ripening stage for both Kluai Namwa varieties. Rutin was the major flavonoid found in both Namwa Mali Ong and Nuanchan varieties ranging 136.00–204.89 mg/kg and 129.15–260.38 mg/kg, respectively. Rutin, naringenin, quercetin and catechin were abundant in both Namwa varieties. All flavonoids increased with ripening except for rutin, gallocatechin and gallocatechin gallate. There were no significant differences (p < 0.05) in flavonoid contents between both varieties. Tannic acid, ellagic acid, gallic acid, chlorogenic acid and ferulic acid were the main phenolic acids found in Mali Ong and Nuanchan varieties, ranging from 274.61–339.56 mg/kg and 293.13–372.66 mg/kg, respectively. Phenolic contents of both varieties decreased, increased and then decreased again during the development stage. Dopamine contents increased from 79.26 to 111.77 mg/kg and 60.38 to 125.07 mg/kg for Mali Ong and Nuanchan, respectively, but the amounts were not significantly different (p < 0.5) between the two Namwa varieties at each ripening stage. Inulin as fructooligosaccharide (FOS) increased with ripening steps. Production stages of sun-dried banana products showed no statistically significant differences (p < 0.05) between the two Namwa varieties. Therefore, when one variety is scarce, the other could be used as a replacement in terms of total flavonoids, phenolic acid, dopamine and FOS. In both Namwa varieties, sugar contents decreased after the drying process. Sugar contents of the dried products were 48.47 and 47.21 g/100 g. The drying process caused a reduction in total flavonoid contents and phenolic acid at 63–66% and 64–70%, respectively. No significant differences (p < 0.05) were found for total flavonoid and phenolic contents between the dried banana products made from the two Namwa varieties (178.21 vs. 182.53 mg/kg and 96.06 vs. 102.19 mg/kg, respectively). Products made from Nuanchan varieties (24.52 mg/kg) contained significantly higher dopamine than that from Mali Ong (38.52 mg/kg). The data also suggest that the banana maturity stage for production of the sun dried products was also optimum in terms of high nutraceutical level.